2008
DOI: 10.1093/sleep/31.6.881
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Insomnia over One Year: a Longitudinal Study in the General Population in Sweden

Abstract: In summary, the results showed that insomnia is a prevalent condition in the general population associated with negative consequences and is characterized not only by persistence but also by relatively high remission and incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 17 publications
9
60
1
Order By: Relevance
“…Rates of sleep dissatisfaction, without regard to specific sleep diagnosis, also vary widely (10% to 25%) in the adult population. When using more stringent and operational DSM [2] or Epidemiology of Insomnia 6 ICSD [19] diagnostic criteria, prevalence rates tend to cluster between 6% and 10% [6][7][20][21][22]. These highly variable estimates underscore the need to rely on operational definitions and standardized assessment procedures to derive accurate and comparable prevalence rates across studies.…”
Section: Prevalence and Correlates Of Insomniamentioning
confidence: 99%
See 2 more Smart Citations
“…Rates of sleep dissatisfaction, without regard to specific sleep diagnosis, also vary widely (10% to 25%) in the adult population. When using more stringent and operational DSM [2] or Epidemiology of Insomnia 6 ICSD [19] diagnostic criteria, prevalence rates tend to cluster between 6% and 10% [6][7][20][21][22]. These highly variable estimates underscore the need to rely on operational definitions and standardized assessment procedures to derive accurate and comparable prevalence rates across studies.…”
Section: Prevalence and Correlates Of Insomniamentioning
confidence: 99%
“…Nonetheless, incidence rates vary extensively across studies, depending on the case definition (e.g., symptoms vs. syndrome) and the interval used to track new onset. For instance, four population-based studies using the same 12-month interval between baseline and follow-up assessments revealed incidence rates of 2.8% in Sweden [21], 6.0% in the USA [27], 7.4% in Canada [43], and 15% in the UK [44], with the variability being partly accounted for by different case definitions across studies. For example, the Canadian study found an incidence rate of 30.7% for insomnia symptoms compared to 7.4% for an insomnia syndrome [43].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sleep pattern had to be present for at least 3 nights per week. (3) The participant had to report daytime impairment (for symptoms: 'quite much' or more, for function: 'marked negative consequences' or more) [48]. (4) The individual must not meet the criteria for apnea, narcolepsy, restless legs syndrome/periodic limb movement disorder, circadian rhythm disorder, sleepwalking, nightmares or hypersomnia as assessed with the SLEEP-50.…”
Section: Insomnia Disordermentioning
confidence: 99%
“…Evidence from longitudinal studies to support the chronicity of sleep disturbance, however, is more limited. A number of studies have reported some persistence over shorter periods of time in children, adolescents, adults, and the elderly [4][5][6][7][8]. An 8-year UK longitudinal study [9] found that a third of those who reported insomnia symptoms in 1985 were still reporting these 4 years later (1989), and a further 10% of the 1989 survey continued to report insomnia symptoms in 1993.…”
mentioning
confidence: 99%